(untitled) (Journal Of Educational and Psychological Researches, 2015)
In order to specify the features of higher education process and its quantitative and qualitative development in Iraq ; one should look back at its historical process and the need of interesting with it . Accordingly , there will be a chance for verifying the demand of the Iraqi society according to the political , social , and cultural changes especially during the national governance (1932 – 1958 ) . For depicting the most important quantitative and qualitative development of this kind of education the period of 1932 -1958 , and since there is no previous study that tackled this topic , here comes the need of writing this paper . After historical and descriptive analysis of the data and the information supported by the references and the books , the paper concluded the following : • During this period , higher education in Iraq had witnessed the development of several colleges like college of economy and trade 1936 , college of pharmacy 1938 ,college of arts and sciences 1949 ,guiding college 1948, college of agricultural 1950 ,college of dentistry 1953 , college of veterinary medicine 1955 . • Many schools and higher institutes where also established like : college of domestic arts 1932 – 1933 , institutes of fine arts 1936 , institute of Queen Alyaa 1945 , the higher institute of industrial engineering 1950 , the higher institute of physical education 1954. • Sevral college and institutes had also been reopened and the developed . those which already existed in 1932 like : law school 1908 , college of sharia 1912,college of engineering 1917 , higher academy of teachers 1923 ,college of medicine 1927 . • That historical period of the higher education development had also witnessed a quantitative and qualitative growth in preparing students ( males – females ) and instructors in the higher institutes and college , in addition to the growth of quality and the quantity of students missions from Iraq and the other Arabic countries . • That period had also involved the establishment of the first Iraqi University called University of Baghdad. • Several committees had been formed in that period .they discussed the importance of opening several colleges and concentrated on the curricula taught there . they also discussed the means of putting criteria of students acceptance in the college and institutes .